Nat enough - Scrivan, Maria (2020)
Natalie has never felt that she's enough -- athletic enough, stylish enough, or talented enough. And on the first day of middle school, Natalie discovers that things are worse than she thought -- now she's not even cool enough for her best friend, Lily! As Natalie tries to get her best friend back, she learns more about her true self and natural talents. If Natalie can focus on who she is rather than who she isn't, then she might realize she's more than enough, just the way she is
All about me! -- Magazine girl -- Hurdles and other obstacles -- Snoozefest -- Raining cats and frogs -- Hats off -- Cupid strikes again -- Dance (but everyone is watching) -- Sing like no one can hear you -- Costumes, please -- Showstopper -- Smoke and mirrors -- A day in the life -- About time -- What's the story? -- What's for lunch? -- The envelope, please -- Stand up -- A day in the life of a frog if she wasn't made out of Jell-O
Ages 8-12
Keywords: Friendship -- Comic books, strips, etc; Self-esteem -- Comic books, strips, etc; Middle schools -- Comic books, strips, etc; Friendship -- Juvenile fiction; Self-esteem -- Juvenile fiction; Middle schools -- Juvenile fiction; Graphic novels; Comic books, strips, etc; Comics (Graphic works); Fiction; Juvenile works; Graphic novels; Comics (Graphic works); Graphic novels